PROFIL EMOSI IBU POSTPARTUM BERDASARKAN SKOR EDINBURGH POSTNATAL DEPRESSION SCALE: ANALISIS BIBLIOMETRIK GLOBAL 2013–2023 - Rani Darma Sakti Tanjung; Oktaria Safitri (Jurnal Ilmiah Kebidanan Imelda, 2026)
Postpartum emotional disturbances remain a significant global maternal health concern. The Edinburgh Postnatal Depression Scale (EPDS) has been widely used as a screening instrument to assess maternal emotional status during the postpartum period. This study aimed to analyze global research trends related to maternal emotional profiles based on EPDS scores using a bibliometric approach. A bibliometric analysis was conducted using publications indexed in the Scopus database from 2013 to 2023. Data were analyzed using VOSviewer to identify publication trends, citation networks, author collaborations, and keyword co-occurrence patterns. A total of 1,248 articles were identified. The highest number of publications occurred in 2021. The United States, the United Kingdom, and Australia were the most productive countries contributing to EPDS-related research. Keyword analysis revealed several dominant clusters, including postpartum depression, anxiety, social support, screening, and maternal mental health. The findings indicated increasing global attention to early screening and emotional profiling using the EPDS. Bibliometric mapping also demonstrated that EPDS-based research has gradually shifted toward preventive interventions and the development of digital screening tools. In conclusion, this study provides a comprehensive overview of the development of EPDS-related research and highlights the need to strengthen midwifery-based early detection strategies for maternal mental health.